Understanding the lived music listening experiences of adults on the autism spectrum. (May 2023) - Venter, Frans; Morelli, Janelize; Erasmus, Ewie
This study focused on the role music listening experiences play in the lives of three South African adults on the autism spectrum. The purpose of this interpretative phenomenological analysis (IPA) is to understand the role that music listening plays in the lives of three adults living with autism. IPA considers three key areas of philosophical knowledge, which include phenomenology, hermeneutics, and idiography. We, therefore, interpreted the role of music listening for our participants by highlighting similarities and differences between the participants' lived experiences. The findings emerging from this study revealed five superordinate themes explaining the significance of music listening in the adults' lives: (1) coping with auditory sensitivity, (2) getting lost in music, (3) music is a companion, (4) self-regulation, and (5) finding connection. The importance of music for masking or coping with sensory overload is distinct from the studies conducted to understand the music listening experiences of neurotypical individuals. It is our hope that the findings of this IPA provide rich idiographic descriptions of the individual experiences of our participants, thereby humanizing their music listening experiences.